(untitled) (Nigerian Journal of Pharmaceutical Research, 2023)
Background: There has been a rise in social, academic and mental health problems among university students which can be reduced if students have access to counselling services. Objectives: This study sought to assess the involvement of students in counselling activities across federal, state and private schools in Nigeria and determine the barriers students encounter in accessing counsellors. Methods: The study was a cross-sectional survey of undergraduate students in public (Federal and State) and private pharmacy schools in Nigeria. The sample size of 857 students was calculated using Krejcie and Morgan’s formula (1970) and used in the study. A set of pretested questionnaires was validated and administered to respondents. Data was collected and organised using descriptive statistics like frequencies, percentages and weighted averages. Inferential determination was done using statistics like Kruskal-Wallis and Chi-Square (χ2) Tests. Results: The results revealed that 66.9% had not encountered any counsellor and 80.0% had never been referred to a counsellor since they entered pharmacy school. Federal universities had more students who had never been referred to a counsellor since they resumed school (χ2= 6.250, p = 0.04). The barriers to accessing counsellors included issue of confidentiality of the encounter (16.3%), stigma attached to meeting with counsellors (11.5%) among others. Conclusions: Counselling services are available in most pharmacy schools but the students were not properly sensitized to them. Issue of confidentiality and stigma are some of the barriers affecting the willingness of the students to access a counsellor.